Penerapan Metode Brainstorming untuk Meningkatkan Kognitif Peserta Didik IPS Kelas XI SMAN 1 Campurdarat Tulungagung - Agil Wong Haidar; Binti Maunah (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Education plays a central role as the foundation for character development and the enhancement of human resources quality. In SMAN 1 Campurdarat Tulungagung, the 11th-grade social studies class faces challenges that require an improvement in students' cognitive abilities. To address these challenges, it is essential to adopt innovative and effective teaching methods. Therefore, at SMAN 1 Campurdarat Tulungagung, the 11th-grade social studies class is placed at the center of efforts to enhance students' cognitive abilities to prepare them to be competent and competitive individuals. In addressing the learning issues at SMAN 1 Campurdarat, such as students' lack of interest and low motivation in social studies subjects, an economics teacher is required to utilize various methods, such as brainstorming. Brainstorming can be conducted in groups so that students can generate good and creative ideas. This research aims to: 1) Outline the Steps of Implementing Brainstorming Method by Teachers to Enhance Cognitive Abilities of 11th Grade Social Studies Students at SMAN 1 Campurdarat Tulungagung; 2) Analyze the Strategies of Brainstorming Method by Teachers to Enhance Cognitive Abilities of 11th Grade Social Studies Students at SMAN 1 Campurdarat Tulungagung; 3) Assess the Impact of Brainstorming Method by Teachers on Enhancing Cognitive Abilities of 11th Grade Social Studies Students at SMAN 1 Campurdarat Tulungagung for the Academic Year 2023/2024. This research employs a qualitative descriptive method, which derives data from observation, interviews, and documentation. The data analysis technique utilized is the Milen and Hubernan concept, which involves three stages. The findings of this research are as follows: 1. Brainstorming steps include teacher's introduction, greetings and prayers, ice breaking, learning objectives and topics, material explanation, group division, method and rule explanation, distribution of problem sheets, problem explanation, thinking and idea formulation time, idea development, answer writing, reading and classification, and idea evaluation.2. Analyzing brainstorming strategies involves implementation in enhancing classroom participation, improving writing skills, increasing student motivation, and enhancing speaking abilities. 3. The impact of brainstorming method includes enhancing students' cognitive abilities, bringing positive effects, and increasing student enthusiasm for learning.